Development of Accounting Systems Using Blockchain Technology - Chandra Prasadhita; Muhammad Nawawi (Jurnal Riset Akuntansi Terpadu, 2023)
Business organizations need adequate data transparency to produce real time and high quality information. The Double Entry accounting system is considered not enough to provide these things, so development of Triple Entry accounting system is needed. Triple Entry accounting system is closely related to Blockchain. This study uses a systematic literature review that leads to development of accounting systems using blockchain technology. This is because the implementation of the Triple Entry accounting system to store transactions permanently on the blockchain ensures that the sender has the authority to carry out non-reversible transactions using public key cryptography.